EVALUASI PROGRAM GERAKAN KEMBALI BERSEKOLAH TAHUN 2018 – 2022 DI KABUPATEN BREBES - Syu’la, Abidah Nabilah; Astuti, Puji -; Marlina, Neny - (Journal of Politic and Government Studies, 2024)
Gerakan Kembali Bersekolah" (GKB) program in Brebes Regency, initiated in 2017, aims to address Out-of-School Children (ATS) and improve the Human Development Index (HDI) through Extended Schooling Hopes and Average Schooling Duration. However, BPS data for 2022 indicates a low HDI in Brebes Regency. The research employs the CIPP (Context, Input, Process, Product) Stufflebeam evaluation model with a qualitative method, utilizing purposive and snowball sampling. The research findings in context evaluation reveal the strengths and weaknesses of the GKB program, yet these strengths have not effectively addressed the weaknesses. In input evaluation, the strategies implemented by the Brebes Regency Government to address program issues have not been entirely successful. In process evaluation, annual evaluations are carried out as planned, but there are still issues beyond control. In product evaluation, modifications are made to the GKB program to enhance HDI. Thus, it can be inferred that the Brebes Regency Government has not successfully addressed the improvement of the GKB program, despite conducting evaluations annually. Therefore, if the GKB program is to continue, various unresolved issues need to be rectified. Further research is needed on the evaluation of the GKB program using different theories and broader informants to understand the development based on annual evaluations. Keywords: Evaluation, “Gerakan Kembali Sekolah” Program, Human Development Index, Out-of-School Children